Semiotics with Style and Situation: Multi-modal Comparative Analysis of Title pages of Native and Non-native English Novels - Manvender Kaur Sarjit Singh; Muhammad Imran Shah; Eram Jamil; Rabia Feroz (Register Journal, 2021)
The communicative function of text can be obtained through the multimodal analysis of the text which contains the interaction and integration of two or more semiotic resources, graphics and text. This study investigated the structure of the titles and graphics of the title pages along with the situation of the content of native and non-native title pages of English novels of modern age. 20 title pages including 10 modern native and non-native English novels are randomly selected from the Google search engine. Multimodal analysis including Jeffries (2016) model to analyse the structure of the text of the title pages, Davy (2013) model to analyse the graphical features of the title pages and Bernstein (2003) to investigate the situational features presented in the title pages of the novels have been followed.  A bench mark technique was used to identify the graphics of title pages, structure of the title phrases and situation presented in the title pages. The results generated from qualitative analysis indicated that mostly the native authors observed all of the features mentioned by the great linguists, stylitions and graphic experts while selecting the design of title pages whereas, non-native authors and publisher have not kept these features in mind while selecting the contents of title page of their composition. It causes lack of readership as the readers cannot extract maximum information from the title page.  The study has opened new dimensions to the new researchers and it also beneficial for the authors and publisher in the selection of the title pages.Key words: Semiotics, Graphics, Situation, Text, Title-page